From monitoring to near real-time groundwater forecasting: a case study of the Cape Town Table Mountain Group aquifers, South Africa - Gutierrez, Alexis; Mougin, Bruno; Nicolas, Jérôme; Bault, Violaine; Lasher-Scheepers, Candice; Fisher-Jeffes, Lloyd; Msimango, Philani; Ncube, Alexander (Hydrogeology journal, 2025)
Groundwater level monitoring is essential for assessing groundwater dynamics to determine past and future trends. When integrated with models, groundwater level fluctuations can be predicted in the short to medium term using precipitation probabilities or meteorological forecasts. This is the purpose of the ‘MeteEAU Nappes’ tool implemented by BRGM (French geological survey) for the City of Cape Town (CoCT) for the Table Mountain Group Aquifers (TMGA). This case study shows how near real-time groundwater level monitoring can be used to support the municipality in managing future groundwater withdrawals. The TMGA are an important source of groundwater in the Western Cape region of South Africa. The upper Nardouw aquifer of the TMGA is an unconfined to semi-confined aquifer recharged by rainfall. It was monitored in the Steenbras area for over 10 years before the CoCT started groundwater abstraction from the Steenbras Wellfield in 2021. The MeteEAU Nappes forecasting tool is already implemented for many observation wells of the national piezometric network of France where it is used for decision-making by the French administration for measures regarding drought or flood anticipation. It combines real-time hydrological observations with a lumped model (e.g. GARDENIA) to simulate groundwater level and extrapolates observations for the following 6 months from statistical meteorological scenarios combined with abstraction scenarios. This tool can help to protect the TMGA targeted at Steenbras Wellfield as a critical source of water for the CoCT, along with ensuring continued ecological functioning of various groundwater-dependent ecosystems El monitoreo del nivel de las aguas subterráneas es esencial para evaluar su dinámica y determinar las tendencias pasadas y futuras. Cuando se integra con modelos, es posible predecir las fluctuaciones del nivel a corto y medio plazo utilizando probabilidades de precipitación o pronósticos meteorológicos. Este es el objetivo de la herramienta «MeteEAU Nappes» implementada por el BRGM ( Servicio Geológico de Francia ) para Ciudad del Cabo (CoCT) en los acuíferos del Table Mountain Group (TMGA). Este estudio de caso muestra cómo el monitoreo del nivel de las aguas subterráneas en tiempo casi real puede utilizarse para ayudar al municipio a gestionar las futuras extracciones de agua subterránea. Los TMGA son una importante fuente de agua subterránea en la región del Cabo Occidental de Sudáfrica. El acuífero superior de Nardouw de los TMGA es un acuífero no confinado a semiconfinado que se recarga con las precipitaciones. Se ha supervisado en la zona de Steenbras durante más de 10 años antes de que la CoCT comenzara la extracción de agua subterránea del campo de pozos de Steenbras en 2021. La herramienta de predicción MeteEAU Nappes ya se ha implementado en muchos pozos de observación de la red piezométrica nacional de Francia, donde la administración francesa la utiliza para tomar decisiones sobre medidas relacionadas con la anticipación de sequías o inundaciones. Combina observaciones hidrológicas en tiempo real con un modelo concentrado (por ejemplo, GARDENIA) para simular el nivel de las aguas subterráneas y extrapola las observaciones para los seis meses siguientes a partir de escenarios meteorológicos estadísticos combinados con escenarios de extracción. Esta herramienta puede ayudar a proteger la TMGA dirigida al campo de pozos de Steenbras como fuente crítica de agua para el CoCT, además de garantizar el funcionamiento ecológico continuo de diversos ecosistemas dependientes de las aguas subterráneas. La surveillance du niveau des eaux souterraines est essentielle pour évaluer la dynamique des eaux souterraines et déterminer les tendances passées et futures. Lorsqu'elles sont intégrées à des modèles, les fluctuations du niveau des eaux souterraines peuvent être prévues à court et moyen terme à l'aide des probabilités de précipitations ou des prévisions météorologiques. C'est l'objectif de l'outil « MeteEAU Nappes » mis en place par le BRGM (Bureau de recherches géologiques et minières) pour la ville du Cap (CoCT) pour les aquifères du groupe de la montagne de la Table (TMGA). Cette étude de cas montre comment la surveillance en temps quasi réel du niveau des nappes peut aider la municipalité à gérer les futurs prélèvements d'eau souterraine. Les TMGA constituent une source importante d'eau souterraine dans la région du Cap-Occidental en Afrique du Sud. L'aquifère supérieur de Nardouw des TMGA est un aquifère libre à semi-captif alimenté par les précipitations. Il a été suivi dans la région de Steenbras pendant plus de 10 ans avant que la CoCT ne commence à prélever de l'eau souterraine dans le champ captant de Steenbras en 2021. L'outil de prévision MeteEAU Nappes est déjà mis en œuvre pour de nombreux points d'observation du réseau piézométrique national français, où il est utilisé par l'administration française pour prendre des décisions concernant les mesures à prendre en cas de sécheresse ou d'inondation. Il combine des observations hydrologiques en temps réel avec un modèle globalisé (par exemple GARDENIA) pour simuler le niveau des eaux souterraines et extrapole les observations pour les six mois suivants à partir de scénarios météorologiques statistiques combinés à des scénarios de pompage. Cet outil peut contribuer à protéger les TMGA ciblés par le champ captant de Steenbras, source d'eau essentielle pour la CoCT, tout en garantissant le fonctionnement écologique continu de divers écosystèmes dépendants des eaux souterraines O monitoramento do nível das águas subterrâneas é essencial para avaliar a dinâmica das águas subterrâneas e determinar tendências passadas e futuras. Quando integrado a modelos, as flutuações do nível das águas subterrâneas podem ser previstas a curto e médio prazo usando probabilidades de precipitação ou previsões meteorológicas. Este é o propósito da ferramenta "MeteEAU Nappes", implementada pelo BRGM (Serviço Geológico Francês) para a Cidade do Cabo (CoCT) para os Aquíferos do Grupo Table Mountain (AGTM). Este estudo de caso mostra como o monitoramento do nível das águas subterrâneas em tempo quase real pode ser usado para auxiliar o município na gestão de futuras captações de águas subterrâneas. Os AGTM são uma importante fonte de águas subterrâneas na região do Cabo Ocidental, na África do Sul. O aquífero Nardouw superior do AGTM é um aquífero livre a semiconfinado, recarregado pela chuva. A área de Steenbras foi monitorada por mais de 10 anos antes da CoCT iniciar a captação de água subterrânea do Campo de Poços de Steenbras em 2021. A ferramenta de previsão MeteEAU Nappes já está implementada em muitos poços de observação da rede piezométrica nacional da França, onde é usada para a tomada de decisões pela administração francesa em relação a medidas relacionadas à antecipação de secas ou inundações. Ela combina observações hidrológicas em tempo real com um modelo concentrado (por exemplo, GARDENIA) para simular o nível das águas subterrâneas e extrapola observações para os seis meses seguintes a partir de cenários meteorológicos estatísticos combinados com cenários de captação. Esta ferramenta pode ajudar a proteger o AGTM direcionada ao Campo de Poços de Steenbras como uma fonte crítica de água para a CoCT, além de garantir o funcionamento ecológico contínuo de vários ecossistemas dependentes de águas subterrâneas